Modulation of Intrathymic Sphingosine-1-Phosphate Levels Promotes Escape of Immature Thymocytes to the Periphery with a Potential Proinflammatory Role in Chagas Disease - Ana Flávia Nardy (BioMed Research International, 2015)
The sphingosine-1-phosphate (S1P) system regulates both thymic and lymph nodes T cell egress which is essential for producing and maintaining the recycling T cell repertoire. Infection with the protozoan parasite Trypanosoma cruzi induces a hormonal systemic deregulation that has impact in the thymic S1P homeostasis that ultimately promotes the premature exit of immature CD4−CD8− T cells expressing TCR and proinflamatory cytokines to peripheral lymphoid organs, where they may interfere with adaptive immune responses. In what follows, we review recent findings revealing escape of these immature T cells exhibiting an activation profile to peripheral compartments of the immune system in both experimental murine and human models of Chagas disease.